Comparison of silver diamine fluoride and sodium fluoride with functionalised tricalcium phosphate on caries arrest / prevention in early childhood caries and their effects on oral health related quality of life: randomised controlled trial - Arshad, Anas Imran (2024)
Minimally invasive treatment for early childhood caries includes the application of 38% silver diamine fluoride (SDF) and 5% sodium fluoride with functionalised tricalcium phosphate (NaF-fTCP). This study aimed to compare the effectiveness of SDF and NaF-fTCP in arresting and preventing carious lesions in primary molars among preschool children. Specific objectives include determining caries prevalence and risk, comparing oral health-related quality of life, behaviour, and pain experience before and after treatment, assessing differences in caries experience, and comparing carious lesion arrest between the treatments. A randomised controlled trial was conducted among 4-6-year-old preschool children in Pakistan. A total of 41 children were randomised into SDF (n= 35 teeth) and NaF-fTCP (n= 45 teeth) groups. SDF and NaF-fTCP were applied to carious lesions at baseline and 6- and 12-months. Urdu-ECOHIS, behaviour, pain and caries assessments were performed, and statistical analyses (paired t-test, repeated measures ANOVA, Wilcoxon signed-rank test) were used to evaluate outcomes. Of the 782 children, caries prevalence was 44.6% (95% CI, 41.1- 48.1), with a median dfs 4.0 (IQR=9.0). The mean Urdu-ECOHIS scores increased from 6.13 (SD 5.53) at baseline to 7.17 (SD 7.90) at 12 months, but the changes were not significant (p = 0.556). In the child impact section (CIS), the symptom domain showed a significant increase (p = 0.032), while other CIS domains and family impact sections were not significant (p>0.05). The changes in Frankl Behaviour Rating score were not significant (p=0.236) in both groups. The Wong-Baker Pain Rating score showed a significant increase over time for the SDF group (p = 0.012) but not for the NaF-fTCP group (p = 0.085) and was not significant between groups (p = 0.713). In the SDF group, median dfs significantly increased from baseline to 6 months, [5.0 (IQR=9.8), p = 0.005], and 6 to 12 months [6.0 (IQR=9.0), p = 0.039]. Similarly, in the NaF-fTCP group, dfs increased from baseline to 6 months [9.0 (IQR=8.0), p = 0.003] and 6 to 12 months [10.0 (IQR=13.0), p = 0.026]. In the SDF group, 34 (97.1%) of lesions were arrested at 6 months (p = 0.317), decreasing to 27 (80%) at 12 months (p = 0.034). Similarly, in the NaF-fTCP group, 43 (95.6%) of lesions were arrested at 6 months (p = 0.157), decreasing to 36 (82.2%) at 12 months (p = 0.020). Both treatments effectively arrested caries lesions. SDF is preferable for short-term effectiveness, while NaF-fTCP provides comparable longer-term results